Sustainability in the Surgical Center Scenario: Literarura review (Research, Society and Development, 2021)
The Objective: Analyze information about sustainability in the operating room, identifying sustainability strategies. Methodology: Integrative literature review, literature, systematized by the acronym Participant, Interest and Context, according to the PICo strategy and procedures defined by the Preferred Reporting Items for Systematic Reviews and Meta-Analyzes (PRISMA). The databases consulted were: Regional Portal of the Virtual Health Library, LILACS, in the National Library of Medicine's PubMed Medline; Capes Journals Portal: CINAHL (Ebsco), EMBASE (Elsevier), Scopus (Elsevier), Web of Science (Clarivaty Analytics). Publications in Portuguese, English and Spanish were considered without restrictions on the year of publication. Six studies were selected for analysis. Results: The selected studies pointed to sustainability in the operating room in four aspects: waste disposal, anesthetic techniques, use of electrical energy, use of disposable or reusable material. They were published in the period between 2018 and 2020. Descriptive studies produced in the United States, Canada, France and China. Conclusion: The operating room is an important source of aggression to the environment, whether by generating waste or consuming energy. The environmental sustainability proposals applied to the operating room come from individual actions such as riding a bicycle or walking to work. Regarding anesthetic techniques, the use of low flow anesthesia and the use of total intravenous anesthesia are sustainable options. Other sustainable measures include the use of reusable surgical gowns, waste monitoring, donation of batteries, unused medical equipment and supplies for medical missions; night shutdown of anesthesia machines and other equipment.